The Lotus japonicus Ubiquitin Ligase SIE3 Interacts With the Transcription Factor SIP1 and Forms a Homodimer - Feng, Yong; Wu, Ping; Fu, Weiwei; Peng, Liwei; Zhu, Hui; Cao, Yangrong; Zhou, Xinan; Hong, Zonglie; Zhang, Zhongming; Yuan, Songli (Frontiers in Plant Science, 2020)
The symbiosis receptor kinase SymRK plays an essential role in symbiotic signal transduction and nodule organogenesis. Several proteins bind to SymRK, but how the symbiosis signals are transduced from SymRK to downstream components remains elusive. We previously demonstrated that both SymRK interacting protein 1 (SIP1, an ARID-type DNA-binding protein) and SymRK interacting E3 ligase (SIE3, a RING [Really Interesting New Gene]-containing E3 ligase) interact with SymRK to regulate downstream cellular responses in Lotus japonicus during the legume-rhizobia symbiosis. Here, we show that SIE3 interacts with SIP1 in both yeast cells and Nicotiana benthamiana. SIE3 associated with itself and formed a homodimer. The cysteine 266 residue was found to be essential for SIE3 dimerization and for promoting nodulation in transgenic hairy roots of L. japonicus. Our findings provide a foundation for further investigating the regulatory mechanisms of the SymRK-mediated signaling pathway, as well as the biological function of E3 ligase dimerization in nodule organogenesis.